PENGEMBANGAN MODEL PEMBELAJARAN MIND MAPPING BERBASIS OUTDOOR LEARNING DALAM PEMBELAJARAN MENULIS PUISI - Oktaviani, Cahyaning (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2024)
Learning to write poetry is often considered difficult for elementary school students because of the students' lack of motivation, ability to develop ideas and vocabulary. Researchers have developed a learning model that can improve students' ability to write poetry. Learning model “Mind Mapping based on Outdoor Learning” designed to increase student motivation by learning to write fun poetry. The development of the Mind Mapping learning model based on Outdoor Learning was carried out by observing and interviewing learning models carried out in elementary schools in learning to write poetry, analyzing the needs of students and teachers in learning to write poetry, preparing product designs for learning model guides Mind Mapping based on Outdoor Learning. The results of testing the effectiveness of the learning model through the t-test show tcount 4,038 with df 53. The df value is 53 than ttable (0,05:53) is 2,006. tcount > ttable or by looking at the probability value of 0,000 (p < 0,05) then H0 is rejected. This shows that there are significant differences between gain score between the experimental class and the control class. Effect size value (effect size) obtained amounted to 0,62 which means it falls into a category large or high. This shows that the Mind Mapping learning model based on Outdoor Learning can have a high effect on students' ability to write poetry.